(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The purpose of the scientific research is to identify the tourism potential of the Republic of Karakalpakstan. Proposals are made to develop the national crafts of the Republic of Karakalpakstan. Government projects aimed at developing international and domestic tourism are analyzed and compared with statistical data. Mechanisms for the development of national crafts are analyzed. The most favorable types and forms of tourism rich in resources are taken as examples. The strengths, weaknesses, weaknesses and opportunities for implementing projects in the Republic of Karakalpakstan are analyzed.